EFL Teachers’ Perceptions of Classroom Assessment within the Framework of the Merdeka Belajar Curriculum - Bani Amirul; Insan Utama Sinuraya (Pusdikra-Publishing.com, 2026)
This research aims to investigate the common assessment practices employed by teachers in EFL classrooms and explore EFL teachers' perceptions of assessment practices in the implementation of the independent learning curriculum in EFL classes. The participants in the study included nine EFL teachers in senior high school. Using a qualitative descriptive approach, data were collected through semi-structured interviews and questionnaires. The results of this research indicate that teachers utilize formative assessment with various techniques that encourage active student participation in the classroom. Additionally, teachers express that the benefits of implementing formative assessment practices are valuable, particularly in English language teaching. Therefore, the researcher recommends that teachers adopt formative assessment practices in EFL classrooms.